Evaluation of class V composite restorations microleakage in premolars with/without electric current while applying variant dentin bondings - Narges Dorri; Azita Kaviani; Ali Noori (Tehran University of Medical Sciences, 2014)
Background and Aims: The ability of composite restorations to prevent microleakage needs desirable bonding material for proper sealing . The purpose of this study was to evaluate class V composite restorations microleakage in premolars with/without electric current while applying variant dentin bonding in vitro.   Materials and Methods: 120 non-carious human premolars were used for this study and standardized class v cavities were prepared. The tooth roots were cut by discs at a distance of 5 mm from CEJ and pulp tissue was removed. The teeth were divided into six groups of 20. In the first group, electric current was applied, Single bond (3M ESPE, St Paul, MN, USA) with a broom motion attached to the cathode and a sponge containing bonding was used as anode. The used current was 15µA and the Single bond in the second group was used without electricity. Then two bondings PQ1 (Ultradent, Germany) and Optibond solo plus (Kerr, USA) were used with and without electricity. After adhesive application and curing the bonding agents, cavities were restored by a composite (Valux Plus). The root ends were sealed by wax and all teeth surfaces, except 1 mm around the restorations were covered with a nail varnish. The specimens were thermocycled for 1000 cycles and placed in fushin for 24 hours and were then sectioned vertically and examined under a stereomicroscope. Data were scored on a 0-4 scale based on microleakage at the gingival margins and analyzed using Kruskal-Wallis and Mann-whitney test.   Results: Based on the results, the extent of microleakage in the groups of electric current was significantly less than the groups without using the electric current (P=0.05). The lowest degree of microleakage was found in PQ1 group, and the greatest difference between the groups with and without electricity was also found in PQ1 group. Single bond and Optibond Solo Plus with electric current showed a lower degree of microleakge.   Conclusion: The result showed that use of electric current during the application of dental adhesives could reduce the extent of microleakage.